The Effect Of Exchange Rate Towards On Stock Returns Mediated By Fundamental Factors (Study On Stocks Of Telecommunications Sub-Sector Companies Listed On The Indonesia Stock Exchange) - Aria Mandala Putra Ginting; Kurnadi Gularso (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to analyze the effect of the exchange rate on stock returns (SR) mediated by fundamental factors, which are represented by return on assets (ROA), debt equity ratio (DER) and earnings per share (EPS), in listed telecommunications sub-sector industrial companies. on the Indonesian Stock Exchange for the 2015-2022 period. This thesis is also to see how financial signals can influence investor perceptions and their impact on SR. The data used is secondary data obtained from the Indonesia Stock Exchange for telecommunications sub-sector companies for the period 2015-2022 and Bank Indonesia data for the IDR-USD exchange rate. This study uses the exchange rate as the dependent variable, stock returns as the independent variable, and ROA, DER and EPS as mediating variables. The analysis technique using the Structural Equation Model (SEM) approach using Partial Least Square (PLS) software, namely Smart PLS software. The results of the study proved that ROA had a not significant positive effect on SR, DER had a significant positive effect on SR, EPS had a significant positive effect on SR, ER had an insignificant positive effect on ROA, ER had an insignificant negative effect on DER, ER had an insignificant negative effect on EPS and ER has a significant negative effect on SR. Furthermore, ER has no significant positive effect on SR mediated by ROA, ER has no significant negative effect on SR mediated by DER, ER has no significant negative effect on SR mediated by EPS.